Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/11038128.2017.1375009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of time management skills: psychometric properties of the Swedish version

Abstract: Three subscales were detected: the time management subscale with 11 items, the organization & planning subscale with 11 items, and the subscale of regulation of emotions with 5 items, with excellent to acceptable psychometric properties. The conclusions were that: ATMS-S is a valid instrument for self-rating of time management, organization & planning and for the regulation of emotions. ATMS-S can be useful for persons with mental disorders including mild neurodevelopmental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The ATMS-S has subscales measuring three constructs: time management skills (11 items), organization and planning (11 items), and regulation of emotion (5 items). Each item has a four-point rating scale from 1 (never) to 4 (always; Janeslätt et al, 2017). The ATMS-S scores for each subscale were transformed to interval-level ATMS units, ranging from 0 to 100, by means of Rasch analysis.…”
Section: Instrumentsmentioning
confidence: 99%
“…The ATMS-S has subscales measuring three constructs: time management skills (11 items), organization and planning (11 items), and regulation of emotion (5 items). Each item has a four-point rating scale from 1 (never) to 4 (always; Janeslätt et al, 2017). The ATMS-S scores for each subscale were transformed to interval-level ATMS units, ranging from 0 to 100, by means of Rasch analysis.…”
Section: Instrumentsmentioning
confidence: 99%
“…The results of person and item reliability indicated that ATMS items were highly consistent and replicable, but it was probably not measuring only one single trait according to the PCA of the residuals. Consequently, ATMS items were divided into subscales: time management (11 items), organization and planning (11 items), and regulation of emotion (5 items) based on the Swedish findings [15] in order to explore whether the same structure holds. Items 3, 4, and 27 which 3 Occupational Therapy International illustrated misfit in both the Swedish and English versions were omitted.…”
Section: Resultsmentioning
confidence: 99%
“…The ATMS is a self-reported 30-item questionnaire aimed at measuring how and how much people adapt their behavior to manage time in daily life [ 14 ]. Recently, a Swedish version of the ATMS (ATMS-S) was developed by our research group [ 15 ], by translating and adapting it culturally and conceptually to Swedish society. The instrument was also adapted to an expanded target group including individuals with neurodevelopmental or mild intellectual disability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] These skills also help in the transition of a medical student to a physician when he realizes that his time is no more his own, at such a point, TMS awareness may be savior. [8,9] Time management requires understanding regarding a blend of structured and unstructured time-consuming tasks followed by fragmenting them according to priorities and then managing them systematically. [10] There is a lack of standard methods to impart the skills of time management to students; rather this skill is learned by observing the seniors or others whom students idealize.…”
Section: Introductionmentioning
confidence: 99%